Heteroatoms-Doped Porous Carbon Derived from Tuna Bone for High Performance Li-S Batteries. (20th December 2017) - Ai, Fei; Liu, Naiqiang; Wang, Weikun; Wang, Anbang; Wang, Feng; Zhang, Hao; Huang, Yaqin
Abstract: Nowadays, the practical application of Li-S batteries is still inhibited by its inferior cycle stability caused by the shuttle effect. Herein, we report the design and fabricate of a fishbone based porous carbon (FBPC) for ultralong cycle life Li-S batteries. Prepared by carbonizing the tuna bone with activation process, FBPC is a heteroatoms-doped hierarchical porous carbon material which owns following merits: i) micropores of FBPC confine the dissolved polysulfides and offer adequate electrochemical reaction interface; ii) mesopores of FBPC not only facilitate infiltration of the electrolyte but also accommodates the volume expansion/contraction during the discharge/charge process; iii) the doped N/S/O heteroatoms increase the reactive sites, present strong polysulfides binding and improve the electroconductivity of carbon matrix. Li-S batteries with FBPC separator exhibit excellent cycling stability (0.064% capacity fading per cycle at 1C) and deliver a high discharge capacity of 1397.5 mAh g −1 at 0.2C. Even after 700 cycles the capacity still retain as high as 599.9 mAh g −1 at 1C. These superior performances as well as abundant precursor and facile preparation process represent the promising prospect of the designed FBPC being applied to the high-performance Li-S batteries. Graphical abstract: Carbonizing the tuna bone to acquire heteroatoms-doped porous carbon materials, and coating this as-prepared material on the PP separator for ultralong cycle life Li-S batteries. Highlights: micropores of FBPC confine the dissolved polysulfides and offer adequate electrochemical reaction interface; mesopores in FBPC facilitate infiltration of the electrolyte and accommodate the volume expansion/contraction during the discharge/charge process; the doped N/S/O heteroatoms present strong polysulfides binding, increase the reactive sites and enhance the electroconductivity of carbon; Li-S batteries with FBPC modified separator achieved ultralong life span and excellent electrochemical performance.